Maternal diet of polyunsaturated fatty acid influence the physical and neurobehaviour of rat offspring. Issue 71 (14th September 2018) - Yang, Rui; Liu, Shao; Zheng, Yi; Zhang, Mengqi; Dang, Ruili; Tang, Mimi
Abstract: Background: Polyunsaturated fatty acids (PUFAs) are normal components of growth and development and its derivatives especially n‐3 PUFAs have an influence on the development and maturation of nervous system. The purpose of our present study was to investigate the effect of maternal n‐3 PUFAs dietary on physical maturation and the neurobiological development of the rat offspring. Methods: According to the content of n‐3 PUFAs in their diets, female dams were randomly divided into three treatment groups (n = 6–7): deficiency, control and supplementation. The physical parameters and neurobehavioral tests were measured in the rats' offspring. Results: There were no significant differences in litter size and sex ratio between three groups. However, the ratio of brain/body weight was higher in the deficiency pups than the control. As to the body weight, the deficiency pups were heavier than the control pups on postnatal day (PND) 1, PND7, PND14, and PND21, while supplementation pups were lower than the control pups on PND1. There are no significant differences in the physical parameters of incisor eruption and fur appearance between three groups. However, deficiency pups had earlier eye opening than the control pups. Unfortunately, there were no significant differences in surface righting reflex, cliff avoidance, forelimb grip and air righting reflex. Whereas, supplementation pups required less time to complete negative geotaxis than the control pups on PND17. Conclusion: This study suggests that the consumption of adequate n‐3 PUFAs is benefit for the optimal growth and development of rat offspring. The n‐3 PUFAs supplementation is beneficial to population that did not have sufficient provision of n‐3 PUFAs in the diet during gestation and lactation.